Probing the Structure and Function of the Cytosolic Domain of the Human Zinc Transporter ZnT8 with Nickel(II) Ions - Catapano, Maria Carmen; Parsons, Douglas S; Kotuniak, Radosław; Mladěnka, Přemysl; Bal, Wojciech; Maret, Wolfgang (International journal of molecular sciences, 2021)
The human zinc transporter ZnT8 provides the granules of pancreatic β-cells with zinc (II) ions for assembly of insulin hexamers for storage. Until recently, the structure and function of human ZnTs have been modelled on the basis of the 3D structures of bacterial zinc exporters, which form homodimers with each monomer having six transmembrane α-helices harbouring the zinc transport site and a cytosolic domain with an α,β structure and additional zinc-binding sites. However, there are important differences in function as the bacterial proteins export an excess of zinc ions from the bacterial cytoplasm, whereas ZnT8 exports zinc ions into subcellular vesicles when there is no apparent excess of cytosolic zinc ions. Indeed, recent structural investigations of human ZnT8 show differences in metal binding in the cytosolic domain when compared to the bacterial proteins. Two common variants, one with tryptophan (W) and the other with arginine (R) at position 325, have generated considerable interest as the R-variant is associated with a higher risk of developing type 2 diabetes. Since the mutation is at the apex of the cytosolic domain facing towards the cytosol, it is not clear how it can affect zinc transport through the transmembrane domain. We expressed the cytosolic domain of both variants of human ZnT8 and have begun structural and functional studies. We found that (i) the metal binding of the human protein is different from that of the bacterial proteins, (ii) the human protein has a C-terminal extension with three cysteine residues that bind a zinc(II) ion, and (iii) there are small differences in stability between the two variants. In this investigation, we employed nickel(II) ions as a probe for the spectroscopically silent Zn(II) ions and utilised colorimetric and fluorimetric indicators for Ni(II) ions to investigate metal binding. We established Ni(II) coordination to the C-terminal cysteines and found differences in metal affinity and coordination in the two ZnT8 variants. These structural differences are thought to be critical for the functional differences regarding the diabetes risk. Further insight into the assembly of the metal centres in the cytosolic domain was gained from potentiometric investigations of zinc binding to synthetic peptides corresponding to N-terminal and C-terminal sequences of ZnT8 bearing the metal-coordinating ligands. Our work suggests the involvement of the C-terminal cysteines, which are part of the cytosolic domain, in a metal chelation and/or acquisition mechanism and, as now supported by the high-resolution structural work, provides the first example of metal-thiolate coordination chemistry in zinc transporters.
Keywords: vztahy mezi strukturou a aktivitou; Zinc Transporter 8; proteinové domény; Humans; Structure-Activity Relationship; nikl; molekulární konformace; Protein Conformation, alpha-Helical; transportní proteiny; diabetes mellitus 2. typu; zinek; Insulin-Secreting Cells; Insulin; Molecular Conformation; Diabetes Mellitus, Type 2; inzulin; lidé; Carrier Proteins; Zinc; zinkový transportér 8; Nickel; Protein Domains; konformace proteinů, alfa-helix; beta-buňky